A high-quality Oxford Nanopore assembly of the hourglass dolphin ( Lagenorhynchus cruciger) genome - McGrath, Nick; le Roux, Jamie; Whibley, Annabel; Alexander, Alana; Stewart, Ramari Oliphant; Johnstone, Muriel; Stockin, Karen A; Silander, Olin K (G3: Genes, Genomes, Genetics, 2025)
Abstract The hourglass dolphin (Lagenorhynchus cruciger) is a small cetacean species of the Southern Ocean, with significance to iwi Māori (Māori tribes) of Aotearoa New Zealand as taonga (treasured/valued). Due to the remoteness and difficulty of surveying Antarctic waters, it remains one of the least-studied dolphin species. A recent stranding of an hourglass dolphin represented a rare opportunity to generate a genome assembly as a resource for future study into the conservation and evolutionary biology of this species. In this study, we present a high-quality genome assembly of an hourglass dolphin individual using a single sequencing platform, Oxford Nanopore Technologies, coupled with computationally efficient assembly methods. Our assembly strategy yielded a genome of high contiguity (N50 of 8.07 Mbp) and quality (98.3% BUSCO completeness). Compared to other Delphinoidea reference genomes, this assembly has fewer missing BUSCOs than any except Orcinus orca, more single-copy complete BUSCOs than any except Phocoena sinus, and 20% fewer duplicated BUSCOs than the average Delphinoidea reference genome. This suggests that it is one of the most complete and accurate marine mammal genomes to date. This study showcases the feasibility of a cost-effective mammalian genome assembly method, allowing for genomic data generation outside the traditional confines of academia and/or resource-rich genome assembly hubs, and facilitating the ability to uphold Indigenous data sovereignty. In the future, the genome assembly presented here will allow valuable insights into the past population size changes, adaptation, vulnerability to future climate change of the hourglass dolphin and related species.